2008
DOI: 10.1002/hep.22423
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory stress exacerbates lipid accumulation in hepatic cells and fatty livers of apolipoprotein E knockout mice

Abstract: The prevailing theory in non-alcoholic fatty liver disease (NAFLD) is the "two-hit" hypothesis. The first hit mainly consists of lipid accumulation, and the second is subsequent systemic inflammation. The current study was undertaken to investigate whether inflammatory stress exacerbates lipid accumulation in liver and its underlying mechanisms. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
156
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(172 citation statements)
references
References 27 publications
13
156
1
2
Order By: Relevance
“…Results similar to ours have been found in liver cells, where TNF-␣ and IL-1 caused a marked decrease in retinoid X receptor ␣, PPAR␣, PPAR␥, LXR␣ and SREBP-1c (97). In the liver of apoE knockout mice and in HepG2 cells, inflammatory stress inhibited PPAR␣ and LXR␣ but increased cholesterol accumulation and SREBP-2 (98). Similarly, hepatic mRNA levels of LXR and retinoid X receptor together with their target genes were rapidly decreased by LPS and proinflammatory cytokines in rodents during the acute phase response (99).…”
Section: Discussionsupporting
confidence: 89%
“…Results similar to ours have been found in liver cells, where TNF-␣ and IL-1 caused a marked decrease in retinoid X receptor ␣, PPAR␣, PPAR␥, LXR␣ and SREBP-1c (97). In the liver of apoE knockout mice and in HepG2 cells, inflammatory stress inhibited PPAR␣ and LXR␣ but increased cholesterol accumulation and SREBP-2 (98). Similarly, hepatic mRNA levels of LXR and retinoid X receptor together with their target genes were rapidly decreased by LPS and proinflammatory cytokines in rodents during the acute phase response (99).…”
Section: Discussionsupporting
confidence: 89%
“…Several lines of evidence demonstrate that exposure to a HFD and diet-induced obesity lead to overproduction of proinflammatory cytokines such as TNF-α and excessive release of FFA, which are both believed to be critical in the progression of NAFLD [35,36] , as well as for the development of insulin resistance [36] . Indeed, our data showed that rats fed a HFD for 16 weeks exhibited a significant increase in serum TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…S.c. casein injection is an established method for the induction of chronic systemic inflammation in mouse models. This has been used in many studies of atherosclerosis and liver steatosis (Miura et al 1985, Wal 2002, Ma et al 2008. In comparison with other sole cytokine or lipopolysaccharide (LPS)-induced mouse models, casein injection induces a lower degree inflammatory stress characterized by increased multiple cytokines (IL1b, TNFa, and IL6) and SAA (like CRP in human) levels in serum, which is more likely to mimic chronic systemic inflammatory state observed in patients with inflammatory stress (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%